Policy document and brief for engagement with government and private sector in Cocoa: A case of Ghana - Dalaa, Mustapha Alasan; Asare, Richard; Mensah, Christian; Naponen, Martin; Saeed, Abdul Razak (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2019)
There is a gap today in funding for investment in developing countries. A recent assessment of financing in the agriculture sector in Ghana based on existing financial sector laws showed that, there is currently no distinct policy to enable lending to the agricultural sector. However, with an ever increasing need to address the challenges of climate change, the need for such policies and resulting finance opportunities for smallholder farmers and other supply chain actor will only increase and become more urgent. Unchanged, most needed investments to address the growing challenges will be made by the private sector or by the farmers themselves. Therefore, public actors, including COCOBOD, need to play a key role in building an enabling environment, including the development of supportive policies, institutions and making matching-funds available. Reducing supply chain risk and improving resilience through such efforts that signal a more secure and favourable framework is key to enabling private actors, especially the more financially vulnerable, to invest. Existing policy initiatives and programs geared towards creating an enabling environment for finance to the sector are currently led by the Ministry of Food and Agriculture (MOFA) and other sector agencies and financial NGO’s